Penerapan Model Pembelajaran Kooparatif Tipe Make a Match dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Ratin Wahyu Juni Atma (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The context of learning Mathematics, students often find it difficult to understand the concepts of KPK and FPB. Appropriate methods are needed to improve students' memory and learning outcomes. The purpose of this study was to determine the effect of applying the make a match type of cooperative learning model on student learning outcomes in mathematics. This study uses Kurt Lewin's CAR Model by using two cycles. The sampling technique was purposive sampling. The sample of this study was 21 students of class IV b SDN 3 Surabaya, East Sakra, East Lombok. The assessment instrument used is a learning test with a KKM of 65%. The analysis technique uses Microsoft Excel. Based on the results of the study, the average student learning outcomes, namely from the first cycle was at 58.57 to 73.33 in the second cycle. The percentage of completeness from 38.09% in the first cycle to 85.71% in the second cycle. The conclusion of this study is that the Make a Match Type Cooperative Learning Model can improve student learning outcomes in mathematics at the KPK and FPB.